GE_GERICHTE C/27105/2011 vom 29. August 2013 - GE Cour de justice (2013)
TRANSFERT DE BAIL; PAS-DE-PORTE; BAIL À LOYER; LOCAL PROFESSIONNEL; ASCENSEUR; USAGE COMMUN ACCRU; JUSTE MOTIF | CO.263.1; CO.263.2